CHARACTERIZATION OF ALGINATE PREPARED FROM BROWN SEAWEEDS IN THUA THIEN-HUE PROVINCE, VIETNAM - Tran Vinh Thien; Chu Dinh Kinh; Tran Thai Hoa; Dinh Quang Khieu (Universitas Gadjah Mada, 2008)
The characterization of alginate prepared from brown seaweeds in TT-Hue province of Vietnam was investigated. Composition and the sequential structure of alginate were determined by 1HNMR, 13C-NMR, TOCSY, 1H-1H COSY, and 1H-13C-HSQC spectrum. It is found that alginate with molecular weight around 101 KDa is composed of homopolymeric regions of M and G blocks, interspersed with very small amount of regions of alternating structure of MG block. This information is essential for application guideline of alginate in TT-Hue province.